2020
DOI: 10.3332/ecancer.2020.1027
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant endocrine therapy for luminal breast cancer treatment: a first-choice alternative in times of crisis, such as the COVID-19 pandemic

Abstract: The epidemiological emergency caused by has changed priorities in breast cancer management. In those places where the pandemic has had the greatest effect, it is of paramount importance for most patients to be at home, reducing or postponing their attendance at clinics, as well as avoiding surgeries. In this scenario, neoadjuvant endocrine treatment could be an appropriate alternative treatment for hormone receptor positive breast cancer (luminal-like tumours) in order to minimise hospital admissions and to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Cancer patients are at an increased risk of contagion, infection, morbidity and death [9][10][11]. Emergency guidelines for breast cancer treatment [13][14][15]32,33] have suggested postponing surgery when the risk of progression is low (luminal tumors), initiating NET, extending the application of NACT and/or target therapies to subtypes of adverse biology (TN and HER2), minimizing the extent of surgery, including avoiding the use of autologous tissue in breast reconstruction, and postponing prophylactic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer patients are at an increased risk of contagion, infection, morbidity and death [9][10][11]. Emergency guidelines for breast cancer treatment [13][14][15]32,33] have suggested postponing surgery when the risk of progression is low (luminal tumors), initiating NET, extending the application of NACT and/or target therapies to subtypes of adverse biology (TN and HER2), minimizing the extent of surgery, including avoiding the use of autologous tissue in breast reconstruction, and postponing prophylactic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic and the emergency recommendations for EBC treatment impacted on the management strategies of Brazilian breast specialists. According to these recommendations [13][14][15]24,32,33], HRpositive EBC should preferentially be treated using NET. Some societies have suggested that recommendations for the treatment of EBC should be classi ed by degree of priority according to the advice provided in the Ontario Health Pandemic Planning Clinical Guideline for Patients with Cancer [37], with cases of luminal tumors being classi ed as Priority B and surgery being postponed for 3-6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triage recommendations estimate the risk of delay‐related outcome compromise. Interventions span deferment, simplification, reorganization of treatment sequence, 7 to pure neo‐adjuvant endocrine therapy in centers with substantial constraints 8 . However, treatment delay can still result in disease upstage, limit surgical options, intensify neo‐adjuvant and adjuvant treatment, and decrease survival 9 .…”
Section: Figurementioning
confidence: 99%
“…Expert groups have drawn up novel protocols for EBC during the pandemic [ 12 14 ]. The treatment of EBC with a low risk of progression, such as ductal carcinoma in situ or invasive hormone-positive tumors, could begin, for example, with neoadjuvant endocrine therapy (NET) [ 15 ]. Surgery would then be postponed with no negative effect on disease outcome [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%